2021
DOI: 10.47144/phj.v54i3.2146
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Radial Artery Occlusion in Patients Undergoing Percutaneous Cardiac Catheterization by Radial Access

Abstract: Objectives: To assess the frequency of radial artery occlusion (RAO) in patients undergoing percutaneous cardiac catheterization. Methodology: A descriptive cross sectional study was carried out at cardiology department Jinnah hospital, Lahore from April – October 2018. One hundred thirty one consecutive patients who had undergone percutaneous cardiac catheterization via the trans-radial approach were enrolled in the study. Post procedure patients were followed in the ward and after 24 hours, Allen’s test was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
1
2
Order By: Relevance
“…Contrary to our findings, a significantly higher proportion of radial artery occlusion has been reported in a study conducted by Butt UM et al 12 in our local population. They included 131 patients who underwent percutaneous cardiac catheterization via the trans-radial approach and 39.7% of them were found to have radial artery occlusion on color Doppler ultrasound after 24 hours of the procedure.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, a significantly higher proportion of radial artery occlusion has been reported in a study conducted by Butt UM et al 12 in our local population. They included 131 patients who underwent percutaneous cardiac catheterization via the trans-radial approach and 39.7% of them were found to have radial artery occlusion on color Doppler ultrasound after 24 hours of the procedure.…”
Section: Discussioncontrasting
confidence: 99%
“…As it has been proven that rate of radial artery occlusion after trans-radial cardiac catheterization is negatively associated with timing of assessment. 8 Hence, the possible explanation for differences in the rates of radial artery occlusion in our study and the study conducted by Butt UM et al 12 is due to the differences in the time of assessment. Similarly, another study by Sadaka MA et al 13 Study further reported radial artery diameter, manual compression, age, and female gender were reported to be independent predictor on multivariable analysis.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Most studies check the pulse to assess radial artery patency before hospital discharge. In the United States, 20% will determine RAO incidence with echo-Doppler or oximetry/plethysmography testing [12,13].…”
Section: Discussionmentioning
confidence: 99%